Substantiation of the indicator the evaluation of options for the distribution forces and means in the organization the security of the base camp by the mobile reserve of the brigade of the defense forces during hostilities - Skopintsev, O.; Tulenko, M.; Kozlov, D.; Koplik, O.; Kramar, O.; Miroshnichenko, P.; Zaharchenko, V. (Grail of Science, 2023)
The work compares and evaluates options for the distribution of forces and means of organizing the security of the base camp during hostilities, therefore, a methodology for the rational distribution of forces and means of security of the base camp by the mobile reserve of the defense force brigade during hostilities has been developed.The probability of holding the base camp was chosen as an indicator for evaluating options for the distribution of forces and resources. The value of the indicator depends on the success of the security organization of the base camp during hostilities. The probability of success of the security organization of the base camp during hostilities will be determined by the initial qualitative ratio of the forces and means of the parties and the coefficient of the degree of fortification equipment of the base camp.
Keywords: brigade of defense forces; distribution of forces and means; organization of security; combat operations